Morte, Espaço e Arquitectura - das Ideias às Formas, um Projecto. - Francisco Manuel Pinto Rocha (2013)
In this thesis, Morte, Espaço e Arquitetura - das Ideias às Formas, um Projeto1, it's proposed a reflection on the Concept of death and its Representations. Including a practical interpretation of the theme by outlining an academic project. One starts by approaching the theme of - the death - by reading into History and using various case studies as a mean to contextualize it. The funerary architecture had an important role on the disclosure of ancient societies's costumes and ways. If in one hand almost all civilizations were lost, the great funerary buildings lasted until the present day, due to their monumental character, allowing us to study and understand the past. The death program in architecture is of equal importance to any other program, and one should note that although it is centered around the cult of dead, it is essentiality a program about the living ones. The main subject is placed in a clear perspective. Here, one can find the presentation for the first Oporto's Tanatório2. Gathering the valences needed to care and sustain the dead and their relatives. In postmodern society in which we operate, it is increasingly common the dematerialization of death, in favor of space and symbols. The architect assumes an important role by designing projects, as the one presented here, that give emphasis to the design of places that welcome people in this particularly hard and special moment of farewell, and that somehow helps them to overcome it. At the same time, the architect finds a practical, hygienic and sustainable solution for the this matter.